2012
DOI: 10.1007/s00520-012-1560-2
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a chemobrain effect for adjuvant FOLFOX chemotherapy in colon cancer patients. A pilot study

Abstract: We found no effect on cognitive function related to chemotherapy, the only little modification is about some emotional performance during chemotherapy. These findings may be explained by the central role of the psychological adaptation process, which occurs during the period from diagnosis to completion of treatment and is characterized by anxiety and adjustment depression. Our results seem to rule out any significant cognitive impairment due to adjuvant FOLFOX4 chemotherapy in colon cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The MMSE test has been used in breast cancer studies to measure dementia (43,44), global cognitive functioning (19), or chemotherapy-and radiotherapy-related cognitive deterioration (45,46). The CDT is a commonly used tool for detecting cognitive deficiency also in cancer patients (47)(48)(49)(50). The depression and anxiety tests, like BDI (12,13,17,40), HDRS (51), STAI-S and STAI-T (6,17,24,40) have been extensively utilized in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The MMSE test has been used in breast cancer studies to measure dementia (43,44), global cognitive functioning (19), or chemotherapy-and radiotherapy-related cognitive deterioration (45,46). The CDT is a commonly used tool for detecting cognitive deficiency also in cancer patients (47)(48)(49)(50). The depression and anxiety tests, like BDI (12,13,17,40), HDRS (51), STAI-S and STAI-T (6,17,24,40) have been extensively utilized in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…One reported no cognitive impairment but was limited by small sample size, lack of a comparator group, use of a brief cognitive battery, and failure to account for practice effect. 6 The other study reported 37% to 39% cognitive impairment before and 6 months after chemotherapy, with a decline from baseline in 52% of participants, particularly in verbal memory. 7 We recently published baseline data from a prospective longitudinal study evaluating cognitive function in patients with CRC, which showed that 43% had objective cognitive impairment shortly after diagnosis, compared with 15% in healthy controls (HCs) without cancer.…”
Section: Introductionmentioning
confidence: 92%
“…This confirms hypothesis 4, that everyday problem solving ability and cognitive functioning are related. (Andreis, Ferri, Mazzocchi, Meriggi, Rizzi, Rota, et al, 2012). Thus it is possible that CRCI simply does not exist in this patient group.…”
Section: Emotional Functioningmentioning
confidence: 88%